The usage and advantages of several common amyotrophic lateral sclerosis animal models - Zhou, Lijun; Xie, Meng; Wang, Xinxin; Xu, Renshi (Frontiers in Neuroscience, 2024)
Amyotrophic lateral sclerosis is a fatal, multigenic, multifactorial neurodegenerative disease characterized by upper and lower motor neuron loss. Animal models are essential for investigating pathogenesis and reflecting clinical manifestations, particularly in developing reasonable prevention and therapeutic methods for human diseases. Over the decades, researchers have established a host of different animal models in order to dissect amyotrophic lateral sclerosis (ALS), such as yeast, worms, flies, zebrafish, mice, rats, pigs, dogs, and more recently, non-human primates. Although these models show different peculiarities, they are all useful and complementary to dissect the pathological mechanisms of motor neuron degeneration in ALS, contributing to the development of new promising therapeutics. In this review, we describe several common animal models in ALS, classified by the naturally occurring and experimentally induced, pointing out their features in modeling, the onset and progression of the pathology, and their specific pathological hallmarks. Moreover, we highlight the pros and cons aimed at helping the researcher select the most appropriate among those common experimental animal models when designing a preclinical ALS study.